An Analysis of Memory Usage in Web Browser Software - Oktavianita, Annisa Dwi; Arifin, Hendra Dea; Fauzi, Muhammad Dzulfikar; Rifa'i, Aulia Faqih (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
A RAM or formerly known as a memory is a primary memory which helps swift data availability without waiting the whole data processed by the hard disk. A memory is also used by all installed applications including web browsers but there have been disappointed in cases of memory usages. Researchers use a descriptive quantitative approach with an observation, a central tendency and a dispersion method. There are 15 browsers chosen by random to be tested with low, medium and high loads to get their memory usage logs. Researchers proceed to analyze the log by using descriptive statistics to measure the central tendency and dispersion of data. A standard reference value from web application memory usage has been found as much as 393.38 MB. From that point, this research is successful and has been found the result. The web browser with the lowest memory usage is Flock with 134.67 MB and the web browser with the highest memory usage is Baidu with 699.66 MB.